2022
DOI: 10.3390/ijerph19052802
|View full text |Cite
|
Sign up to set email alerts
|

Employment, Economic, and Sociodemographic Factors Associated with Changes in Smoking and Drinking Behaviors during the COVID-19 Pandemic in South Korea

Abstract: The societal disruptions resulting from the coronavirus disease 2019 (COVID-19) pandemic may have caused changes in smoking and alcohol consumption. Using data from the Koreans’ Happiness Survey, a nationally representative survey in South Korea, we (1) described population-level smoking and drinking behaviors; (2) assessed changes in smoking and drinking behaviors during the COVID-19 pandemic; and (3) identified employment, economic, and sociodemographic factors associated with these changes using multinomial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Furthermore, some studies have reported increased alcohol consumption during the initial phase of the pandemic [ 26 ]. However, several studies have also found a decrease in alcohol consumption since the implementation of social distancing measures in Korea [ 27 ]. In Korea, the intensity of social distancing measures was adjusted according to the regional severity of COVID-19 [ 28 ]; this may explain our statistically insignificant findings regarding alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have reported increased alcohol consumption during the initial phase of the pandemic [ 26 ]. However, several studies have also found a decrease in alcohol consumption since the implementation of social distancing measures in Korea [ 27 ]. In Korea, the intensity of social distancing measures was adjusted according to the regional severity of COVID-19 [ 28 ]; this may explain our statistically insignificant findings regarding alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the relationship between mandibular fractures and alcohol consumption was proven [ 21 ]. This is thought to be because drinking during the night has decreased due to social distancing and lockdown in Korean society, which has led to fewer fights after drinking [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survey employed a stratified cluster sampling method to ensure representativeness and collected information to describe the happiness level and its inequality in South Korea. Further details of the survey including its sample characteristics have been described elsewhere [ 25 ].…”
Section: Methodsmentioning
confidence: 99%